Establishing and facilitating practice-based interprofessional learning: experiences from the TUILIP project - Penny J. Furness; Helen Armitage; Richard Pitt (MDPI AG, 2012)
The Trent Universities Interprofessional Learning in Practice (TUILIP) project aimed to establish interprofessional learning (IPL) for healthcare students in clinical practice settings. Ten IPL facilitators were employed in eight varied practice setting pilot sites for up to a year to research, develop and run locally appropriate, sustainable IPL initiatives. Following the pilot phase, a qualitative evaluation was conducted in each site by means of interviews or focus groups with all key stakeholders (facilitators, clinical managers, practitioners, students, service users, carers). Data collection was guided by Kirkpatrick’s evaluation framework (1996), which focuses upon participant reactions, and their perceptions of learning, behaviour change and sustainable impact. In keeping with this framework, participants were asked to discuss their experiences of TUILIP in their placement setting (including its facilitation), and their opinions about its impact and success in terms of learning, behaviour change and sustainability. We report a subset of evaluation results relating to the roles of the facilitator, facilitation processes, experiences and challenges, personal and professional impact upon facilitators, and implications for IPL projects in practice. Facilitation tasks included preparing the ground, earning credibility, gathering ideas, researching feasibility, developing initiatives, involving service users, trialling and embedding initiatives. Facilitators were faced with challenges such as getting a focus, time limitations and dealing with logistics. They reported highs (being a fly on the wall, protected time, their educational role, and a sense of satisfaction) and lows (loneliness, frustration and fear of failure), but considered they had developed personally and professionally as a result of their experiences. Results demonstrated the complexity and demands of establishing and facilitating IPL initiatives in practice settings. Facilitation was time-consuming and effortful and did not always achieve its aims, but was a source of satisfaction and personal development. These findings suggest higher education institutions and practice settings should consider carefully the selection, preparation and support for facilitators of practice-based IPL, as well as how to engage local practitioners and service users, and embed changes in the clinical setting.